Improving conceptual understanding of topics in calculus via V-CCMPEDIA - Ahmad, Shamsatun Nahar; Ahmad, Erny Arniza; Mohamad Khalid, Rusnani; Yusri, Muhammad Yassar (Universiti Teknologi MARA, Johor, 2025)
There are certain reasons why new technologies are significant in the domain of the education nowadays, i.e. to offer the utilities of new types of interaction, to avail the learning in a much more absolute free form that might be beneficial to the students in terms of self-learning. The provision of digital pedagogical training on the subject matter will help teachers to overcome the scope of basic technological replacement towards more supercharged digital learning (Rahman & Zain, 2021). Although technological innovation does not have a value of its own, it can only be meaningful when it is the methodology in the tutorial and educational process.